1995
DOI: 10.1159/000168820
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Considerations in Pheochromocytoma and Chronic Hemodialysis: Case Report and Review of the Literature

Abstract: We present a patient on long-term hemodialysis (LTH) discovered to have a pheochromocytoma. A thorough workup pertaining his catecholamine status was performed, and intraoperative catecholamine changes were monitored. This condition poses some analytical difficulties as both interpretation of plasma catecholamine measurements and determination of their metabolic products are impaired. The literature about catecholamines with respect to hemodialysis is reviewed, and the known cases of pheochromocytoma in LTH pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Stumvoll et al (19) noted that in patients with pheochromocytoma receiving long-term HD, CA concentrations were at least 3.3 times higher than the normal values. Therefore, rises in CA concentrations greater than 3 times above normal in patients receiving long-term HD suggest pheochromocytoma.…”
Section: Discussionmentioning
confidence: 98%
“…Stumvoll et al (19) noted that in patients with pheochromocytoma receiving long-term HD, CA concentrations were at least 3.3 times higher than the normal values. Therefore, rises in CA concentrations greater than 3 times above normal in patients receiving long-term HD suggest pheochromocytoma.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma measurements may also be compromised by increased sympathetic outflow or dependence of catecholamine metabolite levels on clearance by the kidneys [9, 10]. These problems are particularly acute in end-stage renal disease (ESRD), when patients are functionally anephric and on dialysis [11]. There 668…”
mentioning
confidence: 99%
“…Stumvoll et al found the NE level was elevated in HD patients, by around 3-fold but never more than that, and the DA level was increased about 2-fold. 10 The E level was not significantly different between the HD group and the control group. Therefore, among long-term HD patients whose plasma CA level increases three times above normal, pheochromocytoma must be considered.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge, 18 cases of pheochromocytoma in association with ESRD have been reported in the English literature (Table 2), [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and resection was performed successfully in all cases. The patients involved were 10 men and eight women, aged 25-59 years (mean age 42.8 years).…”
Section: Discussionmentioning
confidence: 99%